Identification of Persistent RNA-DNA Hybrid Structures within the Origin of Replication of Human Cytomegalovirus - Prichard, Mark N. (American Society for Microbiology, 1998)
Human cytomegalovirus (HCMV) lytic-phase DNA replication initiates at the cis-acting origin of replication, oriLyt. oriLyt is a structurally complex region containing repeat elements and transcription factor binding sites. We identified two site-specific alkali-labile regions within oriLyt which flank an alkali-resistant DNA segment. These alkali-sensitive regions were the result of the degradation of two RNA species embedded within oriLyt and covalently linked to viral DNA. The virus-associated RNA, vRNA, was identified by DNase I treatment of HCMV DNA obtained from sucrose gradient purified virus. This heterogeneous population of vRNA was end labeled and used as a hybridization probe to map the exact location of vRNAs within oriLyt. vRNA-1 is localized between restriction endonuclease sites XhoI at nucleotide (nt) 93799 and SacI at nt 94631 and is approximately 500 bases long. The second vRNA, vRNA-2, lies within a region which exhibits a heterogeneous restriction pattern located between the SphI (nt 92636) and BamHI (nt 93513) and is approximately 300 bases long. This region was previously shown to be required for oriLyt replication (D. G. Anders, M. A. Kacica, G. S. Pari, and S. M. Punturieri, J. Virol. 66:3373–3384, 1992). RNase H analysis determined that vRNA-2 forms a persistent RNA-DNA hybrid structure in the context of the viral genome and in an oriLyt-containing plasmid used in the transient-replication assay.